Expected Return Dan Risiko: Pengujian Consumption-Based Capital Asset Pricing Model (CCAPM) Pasar Saham Indonesia - Saleh, Darwin Zahedy (Universitas Prasetiya Mulya, 2010)
The aim of the study is to assess the positive relation between expected return of asset or portofolio with its consumption beta, using consumption-based capital asset pricing model (CCAPM) (Breden,1979) in Indonesia Stock Exchange market. Hypothesis testing in this research utilizing two-step econometric models: first pass regression and second pass regression. Based on the test, there is no linear and positive relation between expected return and consumption beta. The results suggest the limited correlation between the aggregate of consumption level and historical return movement. The research does not support CCAPM theory. The results indicate another factor aside from consumption in determining stock exchange return. It shows the fact that the small proportion of investor compared to the population of the country affects how the consumption data should be interpreted carefully since the data reflect more on non-investor consumer consumption.